Pengaruh Stress Kerja dan Motivasi terhadap Kinerja Pegawai - Puspita, Santi; Oktariansyah, Oktariansyah (Universitas muhammadiyah palembang, 2021)
This study aims to determine and analyze the effect of work stress and work motivation on employee performance. The research was conducted in one of the Camat offices in Palembang City. The research population is 35 employees. This research is a census study because the number of people studied is as much as the total population. Data was collected using a questionnaire, which was arranged according to the phenomena and objectives expected in this study. Before being distributed to respondents, the questionnaire was tested first through validity and reliability testing. After that, the questionnaire was distributed to the real respondents. To answer this goal, the data analysis used is multiple linear regression analysis. The results of the analysis show that simultaneously, there is a positive and significant effect of work stress and motivation on the performance of X Camat employees in Palembang City. Individually, there is a positive and significant effect of work stress on the performance of X Camat employees in Palembang City. Individually, there is a positive and significant effect of work motivation on the performance of X Camat employees in Palembang City. Because these variables have a significant effect, then to improve employee performance, the most appropriate step is to pay attention to work stress and work motivation.